The Impact Of Toxic Workplace Environments On Employee Productivity: A Systematic Literature Review - Sari, Redha Dian; Dudija, Nidya (International Journal of Science, Technology & Management, 2024)
This systematic literature review aims to evaluate the impact of toxic workplace environments on employee productivity. The methodology involved a comprehensive search and selection of peer-reviewed articles published between 2017 and 2023. The review identifies various forms of toxic behavior, such as harassment, bullying, ostracism, and incivility, and examines how these behaviors affect productivity. The results also indicate that toxic workplace environments significantly increase job stress, leading to decreased employee life satisfaction and productivity. The review highlights the critical role of organizational support in mitigating the negative effects of toxic behaviors. Effective policies and supportive leadership are essential for promoting employee engagement and well-being. The study concludes that addressing toxic workplace environments through strategic interventions and leadership development is crucial for enhancing productivity and overall employee well-being. By recognizing and addressing these issues, organizations can create healthier and more productive workplaces, benefiting both employees and the organization.